2019
DOI: 10.3390/en12102013
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Flow Numerical Simulations on Internal Energy Dissipation for a Low-Head Centrifugal Pump at Part-Load Operating Conditions

Abstract: Dredge pumps are usually operated at part-load conditions, in which the low-solidity centrifugal impeller could experience large internal energy dissipation, related to flow separation and vortices. In this study, SST k-ω and SAS-SST turbulence models were used, in steady and unsteady simulations, for a low-head centrifugal pump with a three-bladed impeller. The main focus of the present work was to investigate the internal energy dissipation in rotating an impeller at part-load operating conditions, related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Based on the above graphical dependencies and previously obtained recommendations [10] on the choice of geometric and kinematic parameters of coaxially installed impellers, it was found that the coaxial arrangement of impellers in centrifugal pumps can reduce hydraulic losses by 23 %, and also contribute to an increase in pressure-fl ow characteristics, with unchanged overall dimensions of the unit.…”
Section: Outer Impellermentioning
confidence: 87%
See 1 more Smart Citation
“…Based on the above graphical dependencies and previously obtained recommendations [10] on the choice of geometric and kinematic parameters of coaxially installed impellers, it was found that the coaxial arrangement of impellers in centrifugal pumps can reduce hydraulic losses by 23 %, and also contribute to an increase in pressure-fl ow characteristics, with unchanged overall dimensions of the unit.…”
Section: Outer Impellermentioning
confidence: 87%
“…When centrifugal pumps are not fully loaded, the pump impeller may experience internal energy dissipation due to fl ow separation and fl uid vortices. In order to establish the characteristics of the processes of dissipation of the internal energy of a centrifugal pump with a partial load, the authors of the article [10] investigated the unsteady nature of such operating modes.…”
Section: Introductionmentioning
confidence: 99%
“…This direction includes studies devoted to the numerical simulation of unsteady flows in dredge pumps [2], [3]. They give a formalized approach to determining the internal energy dissipation during the rotation of a dredge pump impeller under conditions of its operation with a partial load caused by separation and stalls of the flow.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the flow instability of a multistage centrifugal pump a off-design conditions was investigated by Shibata et al [13]. Pressure pulsations at dif fuser inlet were measured and rotating stall phenomenon was observed with CFD tools In addition, some studies were carried out to do the deep analysis on the unsteady flow phenomena in centrifugal pump, for instance, flow separation [14][15][16], rotating stall [17 19] and recirculation [20,21]. Those directly cause the formation of flow instability pressure pulsations and pump vibration.…”
Section: Introductionmentioning
confidence: 99%